Context-aware publish-subscribe: Model, implementation, and evaluation - Cugola, G.; Margara, A.; Migliavacca, M. (2009 IEEE Symposium on Computers and Communications, 2009)
Complex communication patterns often need to take into account the situation in which the information to be communicated is produced or consumed. Publish-subscribe, and particularly its content-based incarnation, is often used to convey this information by encoding the ldquocontextrdquo of the publisher into the published messages. In this paper we claim that this approach is limiting and inefficient and propose a context-aware publish-subscribe model of communication as a better alternative. We describe a protocol that implements such model in a distributed publish-subscribe middleware, and analyze how it performs w.r.t. traditional content-based routing.